Experimental modal identification of smart composite structure applied to active vibration control. (27th September 2021) - Rodriguez, Jonathan; Collet, Manuel; Chesné, Simon
Abstract: This paper proposes an experimental modal identification method for vibration control of multi-actuators and multi-sensors complex smart structures. The general formulation avoids the difficulty of the coupling coefficients identification in electromechanical systems through a modal reduced-order model and uses first-order polynomials as phase correctors for the numerators of the identified transfer functions. Then, a frequency-shaped linear quadratic controller is designed to control multiple modes on a smart composite structure with integrated transducers. The experimental results obtained in terms of multi-modal vibration control were promising with attenuations up to 20 dB on the target modes, confirming the efficiency of the proposed identification and control method for future applications with more extended and complex composite smart structures.